Program Penerapan Omah Sinau dan Pengaplikasian WiFi dalam Meningkatkan Minat Belajar Siswa di Masa Pandemi - Vina Alviana; Muasomah Muasomah (Jurnal Pengabdian Masyarakat PGSD, 2021)
Omah Sinau is the application of Out of School Education concept where education is designed to teach learning citizens to have skills and or knowledge and experience carried out outside of formal education (schooling). This lesson is addressed to residents of Blarakan Tenggah Kebulen Village, especially RT 003 RW 015 Sapuro Kebulen. Some of the activities carried out were house-to-house socialization in dealing with the ineffectiveness of online learning and educating learning participants with different methods which were carried out in Blarakan Kebulen Village. Considering the low importance of overcoming children's learning boredom, this service aims to help the residents of Sapuro Kebulen in online learning during the COVID-19 pandemic era. The study uses observational research and case studies in following up on observations and interviews with the surrounding community to form Omah Sinau program activities to increase student interest in learning during the current pandemic. As a result, through the activities above, they are able to make the public aware of the ineffectiveness of online learning during this pandemic and can provide knowledge to students regarding the difficulties of overcoming online learning.